2011
DOI: 10.1002/cphc.201100038
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Electronic Spectroscopy Studies of meta‐Aminobenzoic Acid in the Gas Phase Reveal the Origins of its Solvatochromic Behavior

Abstract: A theoretical and experimental investigation of meta-aminobenzoic acid (MABA) in the gas phase is presented, with the goal of understanding counterintuitive observations on the solvatochromism of this "push-pull" molecule. The adiabatic excitation energies, transition moments, and excited-state structures are examined using the complete active space self-consistent field approach (CASSCF and CASPT2), which shows the first excited electronic state of MABA to be of greater charge transfer character than was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…0.3° values were founded for angles showed that perfect match between the XRD and simulated structure, the exception of the C-O-H bond angle. Consequently, calculations of molecular structure are very successful when considering experimental values are taken in crystal structure while calculated values are taken in vacuum media There is well-known fact that, 2-aminobenzoic acid derivatives show two type transformations which are the proton exchange in dimers (Monte and Hillesheim, 2001) and the rotation of carboxyl acid group (Fleisher et al, 2011). To find energy gap values between these transformations, relaxed potential energy surface scan calculations were performed.…”
Section: Molecular Structurementioning
confidence: 99%
“…0.3° values were founded for angles showed that perfect match between the XRD and simulated structure, the exception of the C-O-H bond angle. Consequently, calculations of molecular structure are very successful when considering experimental values are taken in crystal structure while calculated values are taken in vacuum media There is well-known fact that, 2-aminobenzoic acid derivatives show two type transformations which are the proton exchange in dimers (Monte and Hillesheim, 2001) and the rotation of carboxyl acid group (Fleisher et al, 2011). To find energy gap values between these transformations, relaxed potential energy surface scan calculations were performed.…”
Section: Molecular Structurementioning
confidence: 99%